2011
DOI: 10.1128/jvi.01769-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Characterization of the Broad-Host-Range Salmonella Phage PVP-SE1: Creation of a New Phage Genus

Abstract: (Bacterio)phage PVP-SE1, isolated from a German wastewater plant, presents a high potential value as a biocontrol agent and as a diagnostic tool, even compared to the well-studied typing phage Felix 01, due to its broad lytic spectrum against different Salmonella strains. Sequence analysis of its genome (145,964 bp) shows it to be terminally redundant and circularly permuted. Its G؉C content, 45.6 mol%, is lower than that of its hosts (50 to 54 mol%). We found a total of 244 open reading frames (ORFs), represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 81 publications
3
74
0
Order By: Relevance
“…[24][25][26][27] In phage PVP-SE1, only 11 of the codons associated with its 24 tRNA genes were present at a frequency higher than in its Salmonella hosts. 28 In the 5 Acinetobacter phages studied by Jin et al, an association between the presence of tRNA genes and codon usage could only be observed for one Acinetobacter phage, ZZ1, and for only 5 out of the 8 tRNA genes. 4 In the Acinetobacter Acibel004 phage, 16 out of its 22 tRNAs are found in higher frequency in the phage's genome than in its host A. baumannii.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…[24][25][26][27] In phage PVP-SE1, only 11 of the codons associated with its 24 tRNA genes were present at a frequency higher than in its Salmonella hosts. 28 In the 5 Acinetobacter phages studied by Jin et al, an association between the presence of tRNA genes and codon usage could only be observed for one Acinetobacter phage, ZZ1, and for only 5 out of the 8 tRNA genes. 4 In the Acinetobacter Acibel004 phage, 16 out of its 22 tRNAs are found in higher frequency in the phage's genome than in its host A. baumannii.…”
Section: Codon Versus Amino Acid Usagementioning
confidence: 99%
“…Further testing is required to determine whether the engineered bacteriophage can be used for field-deployment. Although many different types and phage strains have been isolated from the environment, and while the application of these bacteriophage for the purposes of gene typing and water quality indication have been well studied [41][42][43], the application of isolated bacteriophage or engineered bacteirophage for bioremediation has not yet explored. Therefore the study reported here offers initial data and analysis useful to the applications of bacteriophage for uranium bioremedia tions at Cr and U contaminated sites such as those managed by the US Department of Energy.…”
Section: Discussionmentioning
confidence: 99%
“…Felix 01 is characterized by its broad lytic spectrum among Salmonella and has been used as a diagnostic tool in the identification of Salmonella. Recently, a phage with a broader host range than Felix 01 has been described which presents great potential not only as a therapeutic agent but also as a diagnostic tool Santos et al, 2011;Sillankorva et al, 2010) (Figure 2). Fig.…”
Section: Salmonellamentioning
confidence: 99%